Prosedur Pelaksanaaan Take Over Kredit Umum Pensiun (KUPEN) Di PT Bank Woori Saudara KCP Banyuwangi - Zulvi Lailatul Hidayah; Yoga Adi Saputra (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Currently, there are many kinds of financial institutions that provide various products, namely funding, landing and services. Credit is one of the products from lending services that is very popular with customers because of its many benefits. Credit services are usually used by customers for business capital purposes so that they can encourage economic growth in Indonesia. A banking institution is a financial institution that provides loan or credit services. Bank Woori Saudara KPC Banyuwangi is a banking financial institution that provides services with many superior products, one of which is General Pension Credit (KUPEN) which is specifically for Retired Civil Servants. Apart from that, BWS KCP Banyuwangi also offers a Take Over system for loans from other banks to Bank Woori, KCP Banyuwangi. The results of this service and research aim to ensure that the public, especially retired civil servants, know the procedures and completion of the General Pension Credit Take Over (KUPEN) system from other banks to Bank Woori Brother KCP Banyuwangi. The method used in this research is participatory so that data collection uses observation, interviews and documentation methods. Based on the results of community service regarding the procedures for implementing General Pension Credit Take Over (KUPEN) at Bank Woori Saudara KCP Banyuwangi, there are conclusions that can be drawn, including that the part involved in implementing General Pension Credit Take Over (KUPEN) is the Unit Head, Relationship Officer (RO), Back Office (BO), and TASPEN.